PELAKSANAAN PEMBELAJARAN BERNYANYI SECARA UNISONO DALAM MATA PELAJARAN SENI BUDAYA DI KELAS VII-3 SMP NEGERI 2 KECAMATAN GUGUAK KABUPATEN LIMAPULUH KOTA - Yuliani Lestari; Syeilendra Syeilendra; Harisnal Hadi (SENDRATASIK UNP, 2018)
AbstractThe purpose of this study was to describe the implementation of unison singing lessons in cultural arts subjects in class VII-3 of SMP Negeri 2 Kecamatan Guguak wich was related to the planning, implementation, and evaluation of cultural arts learning. The type of this research was qualitative describtive research.the object of this research was the teacher of cultural arts, students and the implementation of cultural arts learning in class VII-3 at SMP Negeri Kecamatan Guguak. Techniques of data collection where done by observation, interview and location documents. Data where analized using data processing techniques consisting of primary and secondary data. The results should that the implementation of culture art learning at SMP Negri 2 Kecamatan Guguak has not run well in accordance with the draft of syllabus and RPP made by the teacher. In the process of implementation, there where also difficult ties of some student while reading the musical not numbers. Its due to not learning the culture art in elementary school.in order to overcome thie problem, the teacher gave the motivation by a singing the students for many exercises at home. By doing repetitive exercices, it was found better results where students can finnaly  sing unison songs. In conclusion, the result of the learning process has not been achieved one hundred percent. Keywords: learning, Unisono, singing, art and culture